Formulation and Evaluation of Orodispersible Tablets of Zolmitriptan - Balakrishna, T. (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The aim of this study is to formulate and evaluate zolmitriptan orodispersible tablets using novel excipients. Zolmitriptan is an antimigraine drug used in the treatment of migraine. Materials and Methods: In the present investigation, an attempt has been made to enhance the solubility and dissolution rate of zolmitriptan by formulating it as orodispersible tablets were compressed as tablets using superdisintegrants such as croscarmellose sodium and crospovidone. Results and Discussion: Rapid release of zolmitriptan from orodispersible tablets was observed which was influenced by the concentration of superdisintegrants. Among the various tablet formulations prepared with superdisintegrants croscarmellose, 40% showed rapid drug release. The release was found to follow the first order kinetics. The dissolution rate of tablet formulations was found to release the drug at a faster rate than the tablets prepared with plain drug. The drug excipients compatibility was confirmed by Fourier transform infrared and X-ray diffraction studies. No significant changes were observed from these studies.